Protein Kinase C Regulates the Cell Surface Activity of Endothelin-Converting Enzyme-1 - Smith, A. Ian (Kluwer Academic Publishers, 2006)
The potent vasoconstrictor endothelin is a 21 amino acid peptide whose principal physiological function is to regulate vascular tone. The generation of endothelin is crucially dependent on the local presence and activity of endothelin converting enzyme-1 (ECE-1) expressed on the surface of vascular endothelial cells. In this study, we have shown in endothelial cells that the enzyme is phosphorylated, and that phosphorylation is increased by phorbol ester stimulation of protein kinase C (PKC). Furthermore, by monitoring specific ECE-1 activity on the surface of live cells, we also show that following PKC activation, enzyme activity is significantly increased at the cell surface, where it is positioned to catalyse the generation of active endothelin. We believe this novel finding is unprecedented for a peptide processing enzyme. Indeed, this new knowledge regarding the control of endothelin production by regulating ECE-1 activity at the cell surface opens up a new area of endothelin biology and will provide novel insights into the physiology and pathophysiology of endothelin and endothelin-associated diseases. In addition, the information generated in these studies may provide valuable new insights into potential extra- and intracellular targets for the pharmacological and perhaps even therapeutic regulation of endothelin production and thus vascular tone.